Tutela e efetividade dos direitos trabalhistas no procedimento licitatório: esteios de sustentabilidade e ressignificação - Mila Batista Leite Corrêa da Costa (2012)
The public bidding, classic administrative institute, is an administrative procedure used by public authorities to select the best proposal suited to protect and maintain public interest, when Public Administration needs to establish property acquirement or disposal, set contract labor and services, including advertising, and promote concessions, permissions and locations. It is a constitutional imposition, regulated by Federal Law n. 8.666, dated June 21, 1993, to ensure compliance with the principle of equality, selection of the best proposal to the Administration and promotion of sustainable national development. Public bidding should beprosecuted and judged in accordance with the following principles: legality, impersonality, morality, equality, publicity, administrative probity, attachment to the bidding terms and conditions, objective judgment and other related to public competition. The research focusedon the protection and the effectiveness of labor rights in the bidding process and in the execution of public service contracts, emphasizing the need to protect labor rights by the state, considering the constitutional principles; the conceptual redefinition of public interest andAdministrative Law, in postmodern context; and the inclusion of sustainability in the legal text as an objective and bidding guiding principle. The principle and new institute "sustainable bidding" stresses the need of a conceptual resemantization concerning the bestproposal to transform bidding in a true democratic instrument, setting degrees of legal certainty, but, essentially, social justice, especially when is involves human labor. The theoretical-methodological aspect used was the legal-dogmatic, by focusing on elements within the legal system, attempting to understand the normative relations in legal analysis. Itis an interdisciplinary study, an important dialogue between fields of Law Administrative Law and Labor Law as well as a dialogue with bourdieusian sociology, and a possible revision of traditional forms of interpretation, focusing on rights effectiveness.